Immunogenicity and safety of a new live attenuated herpes zoster vaccine (NBP608) compared to Zostavax® in healthy adults aged 50 years and older. Issue 27 (12th June 2019) - Choi, Won Suk; Choi, Jung Hyun; Jung, Dong Sik; Choi, Hee Jung; Kim, Yeon-Sook; Lee, Jacob; Jang, Hee-Chang; Shin, Eui-Cheol; Park, Jun-Sik; Kim, Hun; Cheong, Hee Jin
Abstract: A multi-centre, randomised, double-blinded, active-controlled, parallel-group clinical trial was carried out to assess the immunogenicity and safety of NBP608—a newly developed live-attenuated zoster vaccine in Korea—relative to Zostavax® in healthy adults aged 50 years or older. Immune responses to the vaccine were evaluated by glycoprotein enzyme-linked immunosorbent assay (gpELISA) and enzyme-linked immunosorbent spot (ELISPOT) assays using the interferon (IFN)-γ and interleukin (IL)-2 FluoroSpot kit 6 weeks after vaccination. Safety was monitored for 26 weeks based on subjects' diaries, spontaneous reports from subjects, and history taking by the investigators. A total of 845 subjects participated in the screening, and 823 received the vaccination (413 in the NBP608 group and 411 in the comparator group). The gpELISA-determined geometric mean fold rise from baseline to post NBP608 vaccination was 2.75 [95% confidence interval, CI (2.57, 2.94)]. The gpELISA-determined adjusted geometric mean titers (GMTs) of NBP608 and the comparator were 1346.37 [95% CI (1273.99, 1422.87)] and 1674.94 [95% CI (1585.35, 1769.58)], respectively. The adjusted GMT ratio of NBP608 to the comparator was 0.80 [95% CI (0.75, 0.87)]. There was no statistically significant difference between two groups in terms of the geometric mean spot numbers determined by IFN-γ and IL-2 ELISPOT assays at 6 weeks post vaccination (P = 0.7232, 0.3844). The incidence of adverse events (AEs) within 6 weeks post vaccination was 49.82% overall (410/823, 941 cases), 50.73% (209/412, 474 cases) in the NBP608 group, and 48.91% (201/411, 467 cases) in the comparator group. The difference in AE rate between the two groups was not statistically significant (P = 0.6010). Most AEs were mild, with a rate of 83.12% in the NBP608 group and 75.37% in the comparator group. Thus, NBP608 is non-inferior to Zostavax® in terms of inducing the immune response and can be safely administered to adults aged 50 years or older. ClinicalTrials.gov Identifier: NCT03120364.